Utilization of Medicinal Plants as a Source of Local Herbal Medicine in East Kuripan Village, West Nusa Tenggara - Nurul Patihirrahmi (Alpatih Harapan Semesta, 2025)
Indonesia is one of the tropical countries that is rich in various natural resources such as flora and fauna. Indonesia has the ability to produce medicinal plants because it is a multicultural country with rich natural resources. Medicinal plants are a type of plant that is efficacious and used for traditional medicine. One type of traditional medicine is herbal medicine. Herbal medicine is a traditional herb used by the community to treat minor illnesses and prevent diseases from developing. This study aims to analyze the level of utilization of medicinal plants as ingredients for making local herbal medicine in East Kuripan Village. This study uses a qualitative method that produces descriptive data in the form of written or spoken words from the community. Sampling was carried out using a simple random sampling method in the people of East Kuripan Village. The instrument used in this study is interview guidelines. This study uses a triangulation method that aims to study the same phenomenon and to increase the credibility of the research. Based on the results of interviews that have been conducted with several communities in East Kuripan Village. The researcher obtained interesting information about the manufacturing process, types of herbal medicine, and the benefits felt by the community. The types of herbal medicine obtained are uyup-uyup jamu, sour turmeric jam, kencur rice jam, herbal drinks and 2 types of jamu whose names are not found.